1998
DOI: 10.1002/(sici)1097-461x(1998)68:5<305::aid-qua2>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

New expansion of the Boys function

Abstract: ABSTRACT:We propose a new expansion for the Boys function H t exp yr t dt 0 appearing in the calculation of molecular two-electron matrix elements if Gaussian basis Ž . sets are employed. This expansion involves a power series involving the termsmultiplied by exp y r , where is an optimized parameter g 0, 1 . The performances of the introduced expansion are discussed and illustrated by some numerical experiments. It appears that the proposed expansion is considerably shorter than the customary Taylor series, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…For large values of x , both recursions have the same reported accuracy. Primorac introduced a new expansion of the Boys function that is, however, not part of this study as it was reported by Primorac himself to be inaccurate at higher orders. Other analytical recurrence relations have been derived by Guseinov and Mamedov: Fn(x)=1xktrue[Fnk(x)n+12k12exi=1kxi1n+12kifalse] Fnk(x)=1n+12ktrue[xkFn(x)+12exi=1kxi1n+12kitrue] with k being any integer denoting a recursive offset to n .…”
Section: The Boys Function Kernel Integralmentioning
confidence: 99%
“…For large values of x , both recursions have the same reported accuracy. Primorac introduced a new expansion of the Boys function that is, however, not part of this study as it was reported by Primorac himself to be inaccurate at higher orders. Other analytical recurrence relations have been derived by Guseinov and Mamedov: Fn(x)=1xktrue[Fnk(x)n+12k12exi=1kxi1n+12kifalse] Fnk(x)=1n+12ktrue[xkFn(x)+12exi=1kxi1n+12kitrue] with k being any integer denoting a recursive offset to n .…”
Section: The Boys Function Kernel Integralmentioning
confidence: 99%
“…(1) cannot be expressed in closed analytical form. There exists a solid amount of numerical methods for its evaluation in the literature [4,5,7,[9][10][11]. The most efficient in practical applications are those which rely on pretabulating function values on a dense grid of points and applying relatively short Taylor-type expansions [4,7,12].…”
Section: Introductionmentioning
confidence: 99%